Handbook of research on principles and practices for orchards management - Abobatta, Waleed, 1968-; Farag, Ahmed, 1973-; Abdel-Raheem, Mohamed (IGI Global, 2022)
Looks at how to improve fruit orchardsu0026#39; productivity by exploring the latest practical research findings in the area, and considers the new techniques in various agricultural management practices to improve the growth and productivity of fruit orchards under different biotic and abiotic stresses.